The effect of the servicescape on the customer behavioral intention in Zoo Negara / Rezza Mazlan - Mazlan, Rezza (Faculty of Business and Management, 2007)
Zoo Negara Malaysia is managed by the Malaysian Zoological Society, a non-governmental organization established to create the first local zoo for Malaysians. Zoo Negara is now 44 years old and has matured into a well-known zoo all around the world. It has a total of over 5137 animals from 459 species of mammals, birds, reptiles, amphibians and fish. Its main function is to provide goods and quality services to enhance their customers' satisfaction with their company's motto which is "Research, Education, and Recreational". The main objective of this research is to study on "The Effect of the Servicescape on the Customer Behavioral Intention in Zoo Negara". Further, it is to know whether customers' are aware or not with the services offered by Zoo Negara. For the purpose of this research, the descriptive and causal research was used, 100 questionnaires were distributed to customers of Zoo Negara, and collected using Non-probability Sampling Technique. Questionnaires were distributed as the survey instrument as the source of primary data, other reliable resources would serve as secondary data. This research found that respondents are aware with the services offered by Zoo Negara. Over the years, the zoo has transformed itself to an open concept zoo with over 90% of its animals kept in spacious exhibits with landscape befitting its nature. They are working in making sure that the old zoo concept is changed entirely.